2013
DOI: 10.1088/0967-3334/34/12/1675
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mapping of the effect of knee extension on thigh muscle viscoelastic properties using magnetic resonance elastography

Abstract: Skeletal muscle viscoelastic properties reflect muscle microstructure and neuromuscular activation. Elastographic methods, including magnetic resonance elastography, have been used to characterize muscle viscoelastic properties in terms of region of interest (ROI) measurements. The present study extended this approach to create thresholded pixel-by-pixel maps of viscoelastic properties of skeletal muscle during rest and knee extension in eleven subjects. ROI measurements were taken for individual quadricep mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 80 publications
(114 reference statements)
2
33
0
Order By: Relevance
“…It is worth noting however, that measurements of both |G * | and φ in this study were very similar to measurements that have been made in vivo [23,28,1]. Furthermore, visual comparison of the elastograms produced in silico here with those produced in previous in vivo studies was very favourable.…”
Section: Accepted M Manuscriptsupporting
confidence: 83%
See 3 more Smart Citations
“…It is worth noting however, that measurements of both |G * | and φ in this study were very similar to measurements that have been made in vivo [23,28,1]. Furthermore, visual comparison of the elastograms produced in silico here with those produced in previous in vivo studies was very favourable.…”
Section: Accepted M Manuscriptsupporting
confidence: 83%
“…The elastograms created from the datasets in this study bear strong resemblance to those obtained in vivo, notably the artefacts associated with aliasing at the boundaries in the φ elastograms and the definition of individual muscles in the |G * | elastograms [1,12]. Importantly, definition remained good at noise levels below 5%; estimations in [12] demonstrated that noise for in vivo MRE of the leg was in the region of 2%.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Other studies using similar techniques include Klatt et al,33 and Barnhill et al,34 who reported values for the storage modulus (i.e., G′ ) in the ranges of 0.7 to 2 kPa, and 1.0 to 1.9 kPa, respectively. These data, however, refer to a single frequency acquisition.…”
Section: Discussionmentioning
confidence: 90%